Social support and general self-efficacy: Two predictors of quality of life at work in Ecuadorian teachers - Jaguaco, Diego; Turpo-Chaparro, Josué; Vásquez-Villanueva, Salomon; Apaza-Romero, Abel (Frontiers in Education, 2022)
The quality of life at work has been affected by the COVID-19 pandemic, generating labor overload, higher levels of stress, and a reduction in workers’ productivity. In the education sector, thousands of teachers were affected by the change to a new online work modality and the acquisition of new work tools. The aim of this study was to determine whether social support and general self-efficacy (GSE) significantly predict the quality of life at work in a group of Ecuadorian teachers. A total of 300 teachers of both genders, whose ages ranged between 21 and 64 years, participated in the study. For measurements, the Duke-UNK-11 General Sale Scale and the Scale of Quality of Life in the CVT-Gohisalo Work were used. The predictive analysis was performed through linear regression. The results show a moderately significant relationship between social support, GSE, and quality of life at work. Similarly, the multiple regression analysis confirms that social support and self-efficacy are variables that significantly predict the quality of life at work. The findings of this research also confirm that teachers with higher levels of GSE report higher levels of quality of life at work. In conclusion, the prediction of the variables social support and GSE in the quality of life at work of Ecuadorian teachers is confirmed. The implications of the predictive model mediating quality of life at work are discussed.